Anosmia pada Coronavirus Disease 2019 (Covid-19) - Kiay, Megawati; Pelealu, Olivia C. P.; Mengko, Steward K. (UNIVERSITAS SAM RATULANGI, 2021)
Abstrack: COVID-19 is a disease caused by Coronaviruses (CoVs). WHO has declared the prevalence of COVID-19 as a Public Health Emergency of International Concern (PHEIC). The World Health Organization (WHO) and the Centers for Disease Control and Prevention (CDC) have listed symptoms of anosmia or loss of smell as one of the symptoms of COVID-19 that worth watching out for. This study aims to determine whether there is a relationship between anosmia and the 2019 coronavirus disease (COVID-19). Using the Literature review method, which is carried out by identifying, evaluating and interpreting all the results of certain studies which are the focus of the research. Anosmia is one of the earliest signs of COVID-19 infection with an average onset of 7 days. Symptoms can appear just before, with or immediately after the onset of the usual symptoms, with an average recovery of 14 days. Most patients do not experience nasal congestion or rhinorrhea. There is a relationship between anosmia and coronavirus disease 2019 (COVID-19). Anosmia was found as an early sign of Coronavirus Disease (Covid-19) infection with the average duration of anosmia is 7 days and the results appear to be favorable in less than 28 days. The mechanism of the olfactory disturbance by COVID-19 is not explained. One hypothesis is that SARS-CoV-2 will cause a change of smell through direct access and damage to the CNS through its penetration by the cribriform plate. Another hypothesis is direct viral damage to olfactory cells and taste receptors.Key words: Anosmia, loss of smell, olfactory disorder, coronavirus disease 2019, COVID-19, SARS-Cov2. Abstrak: COVID-19 adalah penyakit yang di sebabkan Coronaviruses (CoVs). WHO telah menyatakan prevalensi COVID-19 sebagai Public Health Emergency of International Concern (PHEIC).World Health Organization (WHO) dan Centers for Disease Control and Prevention(CDC) telah mencantumkan gejala anosmia atau kehilangan kemampuan penciuman sebagai salah satu gejala COVID-19 yang patut diwaspadai. Penelitian ini bertujuan untuk mengetahui apakah ada hubungan anosmia dengan coronavirus disease 2019 (COVID-19). Menggunakan metode Literature review yang di lakukan dengan cara identifikasi, evaluasi dan interpretasi terhadap semua hasil penelitian tertentu yang menjadi fokus penelitian. Anosmia adalah salah satu tanda awal infeksi COVID-19 dengan rata-rata onset 7 hari. Gejala dapat muncul tepat sebelum, bersamaan atau segera setelah timbulnya gejala yang biasa, dengan rata-rata pemulihan 14 hari. Kebanyakan pasien tidak mengalami hidung tersumbat atau rinorea. Ada hubungan antara anosmia dengan coronavirus disease 2019 (COVID-19). Dimana Anosmia di temukan sebagai tanda awal infeksi Coronavirus Disease (Covid-19) dengan durasi rata-rata anosmia adalah 7 hari dan hasilnya tampak menguntungkan dalam waktu kurang dari 28 hari. Mekanisme gangguan penciuman oleh COVID-19 tidak dijelaskan. Salah satu hipotesis adalah bahwa SARS-CoV-2 akan menyebabkan perubahan penciuman melalui akses langsung dan kerusakan pada SSP melalui penembusannya oleh pelat kribriform. Hipotesis lain adalah kerusakan virus langsung pada sel penciuman dan reseptor rasa. Kata Kunci : Anosmia, loss of smell, olfactory disorder, coronavirus disease 2019, COVID-19, SARS-Cov2.